Pension Funds, Capital Controls and Macroeconomic Stability - Reisen, Helmut (OECD Development Centre Working Papers, 1994)
The paper discusses the pros and cons of liberalising foreign investment of pension assets in developing countries, with particular reference to Chile. The positive part of the paper examines the impact on macroeconomic policy of a small country's opening its equity market for investment; the investment strategies of, and the restrictions imposed upon, privately-managed pension funds; and the specific British experience with portfolio diversification after the dismantling of capital controls in 1979. The normative part, while finding only a weak case for regulating foreign pension investment (loss of savings, domestic capital markets), discusses various techniques of such regulation ...